Attaining biochemical euthyroidism early after total thyroidectomy in Graves' disease may lower long-term morbidity risk. Issue 4 (13th July 2022) - Liu, Xiaodong; Wong, Carlos K H; Chan, Wendy W L; Tang, Eric H M; Woo, Yu Cho; Liu, Shirley Y W; Lam, Cindy L K; Lang, Brian H H
Abstract: Background: The relationship between good early control of thyroid hormone levels after thyroidectomy for Graves' disease (GD) and subsequent risks of mortality and morbidities is not well known. The aim of this study was to examine the association between thyroid hormone levels within a short interval after surgery and long-term mortality and morbidity risks from a population-based database. Methods: Patients with GD who underwent complete/total thyroidectomy between 2006 and 2018 were selected from the Hong Kong Hospital Authority clinical management system. All patients were classified into three groups (euthyroidism, hypothyroidism, and hyperthyroidism) according to their thyroid hormone levels at 6, 12, and 24 months after surgery. Cox proportional hazards models were performed to compare the risks of all-cause mortality, cardiovascular disease (CVD), Graves' ophthalmopathy, and cancer. Results: Over a median follow-up of 68 months with 5709 person-years, 949 patients were included for analysis (euthyroidism, n  = 540; hypothyroidism, n  = 282; and hyperthyroidism, n  = 127). The hypothyroidism group had an increased risk of CVD (HR = 4.20, 95 per cent c.i. 2.37 to 7.44, P  < 0.001) and the hyperthyroidism group had an increased risk of cancer (HR = 2.14, 95 per cent c.i. 1.55 to 2.97, P  < 0.001) compared with the euthyroidism group. Compared with patients obtaining euthyroidism both at 6 months and 12 months, the risk of cancer increased in patients who achieved euthyroidism at 6 months but had an abnormal thyroid status at 12 months (HR = 2.33, 95 per cent c.i. 1.51 to 3.61, P  < 0.001) and in those who had abnormal thyroid status at 6 months but achieved euthyroidism at 12 months (HR = 2.52, 95 per cent c.i. 1.60 to 3.97, P  < 0.001). Conclusions: This study showed a higher risk of CVD in postsurgical hypothyroidism and a higher risk of cancer in hyperthyroidism compared with achieving euthyroidism early after thyroidectomy. Patients who were euthyroid at 6 months and 12 months had better outcomes than those achieving euthyroidism only at 6 months or 12 months. Attaining biochemical euthyroidism early after thyroidectomy should become a priority. Abstract : In this retrospective cohort study involving 949 patients with Graves' disease who underwent total thyroidectomy, achieving biochemical euthyroidism early after surgery may lower the long-term risks of morbidities. Therefore, early thyroid function monitoring and control after thyroidectomy is recommended as part of Graves' disease management.